RESPONSE OF LOCAL POTATO CULTIVARS TO LATE BLIGHT DISEASE (Phytophthora infestans (Mont.) de Bary) UNDER FIELD CONDITIONS - Rishav Pandit; Ravi Bhatta; Pooja Bhusal; Basistha Acharya; Subash Subedi; Jiban Shrestha (Universitas Panji Sakti, 2020)
Developing host resistance is an economic and long-term approach to disease management; however, resistance reactions that differ depending on the genotypes. Potato late blight is the devastating disease caused due to Phytophthora infestans (Mont.) de Bary. In order to identify late blight resistance in potato genotypes, seven local potato cultivars (Bardiya Rato Local, Bardiya Seto Local, Cardinal, Deukhuri Rato Local, Deukhuri Seto Local, Kailali Local and Khumal Ujjowal) were evaluated in randomized complete block design (RCBD) with three replications during October 2018 to January 2019 on naturally infested soils in Deukhuri, Dang, Nepal. Results showed that significantly the highest disease incidence (99.17%), and the highest disease severity (88%) were found on Cardinal followed by Deukhuri Rato Local (64%), and Deukhuri Seto Local (60%). Potato cultivar namely Khumal Ujjowal was moderately resistant, whereas Deukhuri Rato local and Deukhuri Seto Local were susceptible to late blight disease. Significantly the highest yield (12.67 t ha-1) was produced by Khumal Ujjowal followed by Bardiya Rato Local (10.78 t ha-1) and Bardiya Seto Local (9.40 t ha-1). The disease incidence and Area under disease progressive curve (AUDPC) value was negatively co-related with the tuber yield. The potato cultivar Khumal Ujjowal followed by Bardiya Rato Local were found moderately resistant to late blight disease in Deukhuri conditions. This study suggests that potato cultivar Bardiya Rato Local can be grown for higher tuber production in Dang and similar topographic regions.DOI: 10.37637/ab.v3i1.464